A Math Educational Computer Game Using Procedural Content Generation - Rodrigues, Luiz A. L.; Bonidia, Robson P.; Brancher, Jacques D. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2017: Anais do XXVIII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2017.756, 2017)
This paper presents an educational game, MentalMath, with the goal of motivating its users to practice math by solving problems. It uses, besides gamification, procedural content generation, which aims to increase the game’s scenarios and problems diversity, tackling some gamification limitations. A preliminary study was conducted with 40 students from a Brazilian school with pre and post written tests, and gameplays data. The results demonstrated that our tool aroused the volunteers’ interest in math, had a higher impact on the ones which played for longer and imposed hard scenarios. We conclude that MentalMath is a reliable tool to motivate children, that our study gave interest insights on its usability and our approach innovates using procedural content generation.